Regulação Androgênica, Atividade Biológica e Sinalização Celular de Beta-Defensinas na Morfogênese do Epidídimo - Ferreira, Lucas Garcia Alves [UNIFESP] (2019)
Reproductive disorders in adult men, a topic of public health interest, may be related to develop-mental and masculinization abnormalities of the male reproductive tract. The mesonephric duct (or Wolffian duct) is an embryonic structure that undergoes a process of tubular-epithelial morphogenesis primarily induced by androgens that originates the epididymis, an essential organ for sperm maturation and function. Disruption of the development of this structure may result in infertility at adulthood, jus-tifying the need for a better understanding of the mechanisms and mediators driving epididymal mor-phogenesis. Our research group has recently identified the β-defensin SPAG11C (sperm associated an-tigen 11 C), a component of innate immunity, as an androgen-dependent mesenchymal factor that mod-ulates the rat mesonephric duct morphogenesis. We have also detected the expression of other β-defen-sins in this tissue. Members of this protein family can promote their effects via Toll-like receptor (TLR) cellular signaling. Taken together, the present aims of the study were to characterize the expression profile and the androgen regulation of a subset of β-defensins in the rat mesonephric duct, to investigate the functional aspects of the DEFB2 (defensin beta 2) and its potential involvement with TLR4 signaling pathway during the prenatal epididymal development, as well as to validate an experimental approach for the detection of recombinant β-defensin processing and secretion in a cell culture model. Our results revealed that the tested β-defensins presented differential gene expression, androgen regulation and cel-lular distribution profile during prenatal epididymal morphogenesis in rat. The β-defensin Defb4 tran-script, the homologue of human DEFB2 (hDEFB2), was negatively regulated between the embryonic days (e) 17.5 and 20.5, a period when the mesonephric duct morphological differentiation occurs. In ducts (e17.5) cultured ex vivo for 96 h, recombinant hDEFB2 reduced duct elongation and coiling as a result of increased cell death in both epithelial and mesenchymal cells. We have also observed that TLR4-induced signaling pathway is present and functional in the mesonephric duct, and its activation by LPS from E. coli can be negatively regulated by hDEFB2. Furthermore, we have validated a Western blot protocol for the detection of SPAG11C protein forms on cell lysate and supernatant from cultured human cells transiently transfected to express this β-defensin. Collectively, these results reveal the par-ticipation of innate immunity components on the scenario of mesonephric duct development, contrib-uting to increased knowledge of the functional repertoire and role of β-defensins in the epididymis and in events related to male fertility.